ENT 600 : Blueprint : Smart intelligence backpack (SiB) / Mohammad Amirulhaikal Mohamed Razali ... [et al.] - Mohamed Razali, Mohammad Amirulhaikal; Habbibollah, Muhammad Haziq; Hussin, Haziq; Sharifuddin, Muhammad Aliff; Eliasa, Muhammad Syazwan (2019)
Backpacks are definitely a must have for people with active lifestyles from students to executive to adventure seekers. A reliable backpack will surely keep their activities running without any problems. Backpack is use for travel, camping and is carried daily for various reason. People can choose another an intelligent yet reliable and organized storage to carry their devices and other daily needs. Thus, the team is developing SiB (Smart Intelligence Backpack), a backpack that is suitable for students and people who are always with their electronic devices